Управління адаптаційним потенціалом підприємства в конкурентному середовищі - Прищепа, Дмитрій Сергійович; Pryshchepa, Dmytrii (ЦНТУ, 2024)
Мета кваліфікаційної роботи полягає у вивченні теоретичних основ адаптаційного потенціалу підприємства; здійсненні оцінки управління адаптаційним потенціалом ТОВ “АВТО-КОМФОРТ ПЛЮС”; формулюванні напрямків удосконалення управління адаптаційним потенціалом підприємства ТОВ “АВТО-КОМФОРТ ПЛЮС”. The purpose of the qualification work is to study the theoretical foundations of the adaptive potential of the enterprise; to assess the management of the adaptive potential of AUTO-COMFORT PLUS LLC; to formulate directions for improving the management of the adaptive potential of the enterprise AUTO-COMFORT PLUS LLC.
Management of the adaptive potential of the enterprise in the competitive environment
Keywords: управління; адаптаційний потенціал; підприємство; конкурентне середовище; management; adaptive capacity; enterprise; competitive environment